Teologi Inkarnasi dan Gereja Yang Inkarnatoris menurut Hans Urs von Balthasar - Anton Dewa (Media (Jurnal Filsafat dan Teologi), 2021)
The uniqueness of Balthasar's theology of incarnation lies in the fact that he bases his arguments of kenosis primarily on the Bible and the theology of patristics. On this basis, he confronts the systematic theological exposition of incarnation with the question of God in modern times. Balthasar represents the centre of his theological principle in the "drama of God". This drama became visible to all men when Christ, Son of God, died for the salvation of the world. That is an act of solidarity and became for Balthasar the central concept of soteriology. Based on the incarnation of Christ, Balthasar calls the church to a living practice of kenosis in her missions.